2020
DOI: 10.1186/s13018-020-01628-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between arthroscopic and open surgery for treatment outcomes of chronic lateral ankle instability accompanied by osteochondral lesions of the talus

Abstract: Background: This study aimed to examine the efficacy and safety of the arthroscopic treatment of osteochondral lesion of talus (OLT) and lateral ankle instability. It was hypothesized that the outcome of all-arthroscopic surgery was no worse than that of the combined open and arthroscopic surgery for treating chronic lateral ankle instability accompanied by OLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…The arthroscopic Broström-Gould procedure is widely used. It involves repair of the lateral ligament complex, and uses the extensor retinaculum to strengthen the repair; at arthroscopy, the intra-articular lesions are addressed, with results comparable to the open Broström-Gould procedure [ 3 , 16 , 23 ]. The classical Broström-Gould procedure has two steps: first, suture of the ATFL and joint capsule repair; second, the imbrication of the extensor retinaculum and suture it over the anterior edge of the fibula [ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The arthroscopic Broström-Gould procedure is widely used. It involves repair of the lateral ligament complex, and uses the extensor retinaculum to strengthen the repair; at arthroscopy, the intra-articular lesions are addressed, with results comparable to the open Broström-Gould procedure [ 3 , 16 , 23 ]. The classical Broström-Gould procedure has two steps: first, suture of the ATFL and joint capsule repair; second, the imbrication of the extensor retinaculum and suture it over the anterior edge of the fibula [ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using suture anchors to the fibula, surgeons can arthroscopically repair the ATFL and augment it with the inferior extensor retinaculum. The Gould modifications can be performed through an accessory anterolateral portal/incision 25,34 or endoscopically (allinside). 12,36 This technique offers an additional diagnostic and therapeutic opportunity for concomitant intraarticular pathologies in the same setting.…”
mentioning
confidence: 99%
“…Ikoma et al [ 26 ] found that CLAI patients with OLT had smaller talus lesions and lower stages (stage 1 and stage 2) than OLT patients without CLAI. The lower grades (1 and 2) of OLTs were associated with better surgical outcomes than the higher grades (3 and 4), and the smaller lesions were associated with better clinical outcomes [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with OLTs less than 15 mm in diameter are usually treated with intra-articular debridement and microfracture [ 1 , 7 ]. In patients with CLAI and OLTs, lateral ankle stabilization and simultaneous surgery for the intra-articular ailment are indicated [ 8 10 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%